(untitled) (Journal of Comparative & International Higher Education, 2022)
This study adopted a systemic perspective to examine the perceived role of academic institutions in responding to Chinese international doctoral students (CIDS) double pandemic experiences. A hermeneutic phenomenological approach was utilized to guide the research process. The results showed the interlocking relations regarding how individual academic experiences interacted with the social-political-institutional environment during this time of crisis. The discussions highlight the systemic influences on CIDS` experiences. The theoretical and practical implications were included in order to inform systemic interventions.